Two new Palearctic mite species of the family Cunaxidae (Acari: Prostigmata) - Kalúz, Stanislav (Zootaxa, 2009)
Two new mite species from SW Slovakia, viz. Armascirus cyaneus sp. nov. and A. cerris sp. nov. (Acari: Prostigmata, Cunaxidae) are described and figured. A key to females of the genus Armascirus of the world is given.